SISTEM MANEJEMEN DAN MONITORING BIMBINGAN TUGAS AKHIR BERBASIS WEB - Salmi; Darmatasia (Prodi Teknik Informatika Universitas Islam Negeri Makassar, 2023)
The process of supervising student final assignments experiences many obstacles that can hinder the process of completing the final assignment itself. In addition, lecturers also carry out other tri-dharma activities, namely research and community service which require lecturers to carry out activities outside the campus. Differences in activity and liveliness between lecturers and students can be one of the obstacles in the final assignment guidance process. The purpose of this research is to design a system that can manage and monitor processes as well as provide advice related to web-based graduation projects, to facilitate processes, suggestions and assurance of information at any time and the accuracy of work processes in improving student graduation performance, especially in the final project process. The results of the accuracy test conducted on respondents and the level of satisfaction of respondents on the feasibility of the system is 80%. Keywords: Management, Guidance, Monitoring, Final Project.. Keywords: Management, Guidance, Monitoring, thesis